Managing, Innovation, Design and Creativity - Stamm Bettina Von (Wiley, 2003)
This book provides managers and students with insights that help them create sustainable and innovative organizations. Introduction, Acknowledgements, A Note on Globalization, What are Innovation and Creativity and Design, Branding and Innovation, The Value of Market Research, A Note to Teams, The Role of Prototypes, Collaborating for Innovation, The Effects of Industry and Cultural Context, Innovation for the Environment, How to Infuse Innovation, Innovation in the Service Industry, Building for Innovation, Putting All these Pieces into Place, The Innovative Organization, References, Index.